(3GdYdGbI GdJHGOdjI Hjf SYQ GdUQa h SYQ GdaGFOI h GfYcGSGJgG Ydi ejRGf GdeOahYGJ (B/s - (3fYeI, SejQ aNQjs; (3ZRGd, ejSQ bGSe s ((3YeGf(B: s (3OGQ GdjGRhQj GdYdejI ddfTQ hGdJhRjY(B, s, 2011)
(3ehKhbjI CSYGQ GdUQa GdYGdejI h fXegG , eaghe h CgejI fXQjGJ GdaGFOI GdJhGRfjI , eVehf h echfGJ ejRGf GdeOahYGJ , aGYdjI h SjGSGJ CSYGQ GdUQa h GdaGFOI aj GWGQ GdGbJUGO Gdcdj , ehGRfI ejRGf GdeOahYGJ aj fXGb fXGej CSYGQ GdUQa h GdaGFOI , UfOhb GdfbO GdOhdj h JTNjU eTcdGJ ejRGf GdeOahYGJ ddHdOGf GdfGejI , OQGSI ebJQMI dJHGOdjI GdYdGbI Hjf SYQ GdUQa h GdaGFOI h EKQgG Ydi ejRGf GdeOahYGJ , GNJHGQ eOi edGAeI SjGSGJ UfOhb GdfbO GdOhdj h CNjQG JbOjQ h JMdjd GdYdGbI GdJHGOdjI Hjf SYQ GdUQa h SYQ GdaGFOI h ZfYcGSgG Ydi ejRGf GdeOahYGJ (B/ (3OQGSI MGdI eUQ ddeOI ef (B1990 (3`` (B2006s
(3HHdjhZQGajG(B: (3U(B.273s
Keywords: (3GdaGFOIs; (3SYQ GdUQas; (3ejRGf GdeOahYGJs